IMPROVING THE CAPABILITY OF SCHOOL SCIENCE LABORATORY MANAGERS THROUGH SCHOOL SUPERVISION ASSISTANCE IN CLUSTER I OF BAGUALA DISTRICT, AMBON CITY - Jotty Sartje Haumahu (EDU SCIENCES JOURNAL, 2020)
This study aims to improve the ability of school science laboratory managers through mentoring school supervisors in cluster I of Baguala district in Ambon City. This research begins with the researchers' findings in the pre-cycle stage where the management of the Natural Sciences Laboratory in 4 of these schools has not been managed properly in accordance with the National Library Standards (SNP: Standar Nasional Perpustakaan). This research is a School Action Research (PTS: Penelitian Tindakan Kelas) conducted in 2 mentoring cycles that contain stages of planning, implementation and reflection (evaluation) and accompanied by a standard of success (minimum of 75%). The results of mentoring in cycle 1 have not shown satisfactory results due to various deficiencies in the mentoring instruments in Junior High School 7 Ambon, Junior High School 13 Ambon, Junior High School 20 Ambon, and Junior High School 21 Ambon. Under these conditions further assistance was made in cycle 2 where the result was that all the mentoring instruments had been repaired and completed by the manager of the school's Science Laboratory. The results of this study indicate that mentoring school supervisors can improve the ability of the Science Laboratory managers in these four schools.